The astigmatism after cataract surgery by corneoscleral and scleral incision methods at Dr. Sardjito Hospital. - Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: Astigmatism change after cataract surgery is common, but if the astigmatism is too high it can affect the visual acuity. The astigmatism change depends on the incision methods, sclera! rigidity, and age.Objectives: To compare the astigmatism change between corneoscieral and sclera! incision methods after cataract surgery and intraocular lens implantation.Methods: Eighty patients after cataract surgery with IOL implantation were evaluated. Keratometry examination was performed pre operative, 2 weeks, 4 weeks, and 8 weeks post operative. All of the patients underwent cataract surgery by fornix base flap conjungtiva, 40 patients were performed corneoscieral incision, and 40 patients were performed sclera! incision. All of them was sutured with ethilon 10.0, consist of 6 stichesResults: The corneoscleral incision induced astigmatisms were 0-8.6 D(dioptri), while the scleral incision was 0-8.50 D. The mean astigmatism of the corneoscieral incision 2 weeks post operative was 3.08 D, 4 weeks was 2.72 D, 8 weeks was 2.13 D, while the astigmatism of the sclera! incision 2 weeks post operative was 3.35 D, 4 weeks was 2.32 D, and 8 weeks post op was 1.75 D. There is no statistical significant difference between the corneoscieral and sclera! incision.Conclusion: The mean astigmatism 2 weeks, 4 weeks, and 8 weeks after operation was decreased in both methods of incisions. Despite no statistical significant difference, the mean astigmatism was lower in scleral incision method.Keywords : astigmatism change - keratometry - cataract surgery - corneoscieral incision - sclera! incision